Space and culture acculturation: Exploring urban regeneration in historic conservation areas, Yangmeizhu Street in Beijing, China - Lanlin Xiang; Changwei Feng; Ying Liu; Yuhong Wang (Frontiers of Architectural Research, 2025)
The regeneration of cultural spaces in historic conservation areas aims to enhance these spaces while preserving their heritage. Achieving sustainable regeneration requires an understanding of the interplay between spaces and their underlying cultures. This study examines the urban regeneration of courtyard spaces on Beijing’s Yangmeizhu Street, using Space Syntax and acculturation theory to explore spatial and cultural attributes. A Kruskal–Wallis H analysis is conducted to investigate the correlation between these features. Findings demonstrate cultural acculturation along Yangmeizhu Street, evaluated through behavior, knowledge, values, and identity. Three typologies emerge: separation (maintaining a unique identity), integration (adopting a broader culture while preserving a distinct identity), and assimilation (complete adoption of the surrounding culture). The assimilation type shows notable differences in spatial characteristics compared to integration and separation. This research highlights the impact of space managers or designers with diverse cultural backgrounds on the transformation of cultural spaces during urban regeneration, revealing contributions from both foreign and indigenous cultures.